KOMISJA WCZESNYCH DZIEJÓW SŁOWIAN IM. PROFESOR A GERARDA LABUDY PRZYMIĘDZYNARODOWYM KOMITECIE SLAWISTÓW - Grzesik, Ryszard (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The texts above, in the chapter “Antique and Medieval Concepts of Slavs Origin” include papers presented during the 16th International Congress of Slavists by members of Prof. Gerard Labuda Commission of Early Slavic History affiliated to the International Committee of Slavists. The main subject of the session was “Antic and Medieval Concepts of Slavic Origin”. Information about the participants and the Commission’s activity is provided with the Statute and a list of members attached.